Performance Evaluation of Crushers in Efforts to Optimise Production Capacity: A Case Study at PT Hoffmen International, Bangkele Site, North Morowali - Suriyanto Bakri; Alfian Nawir; Muhammad Cakrawala Tuhulele (Candela Edutech Indonesia, 2026)
PT Hoffmen International’s Bangkele site in North Morowali has set a crusher production target of 2.5 tonnes per day for processing rocky saprolite-type laterite nickel ore; however, this target is frequently not met. This study aims to evaluate crusher performance, analyse the gap between production targets and actual output, identify limiting factors, and formulate optimisation measures. The research method employs a quantitative descriptive approach with data collection conducted directly in the field through observation and interviews over six working days. The parameters calculated include crusher productivity, Mechanical Availability (MA), Physical Availability (PA), Use of Availability (UA), Effective Utilisation (EU), and equipment effectiveness. The results of the study show that the average actual production reached only 1.42 tonnes per day (56.7% of the target) with an average gap of 1.08 tonnes per day. MA values ranged from 73.42-83.54%, PA from 74.39-85.86%, UA from 81.57-95.08%, EU from 70.73–86.95%, and productivity from 0.16–0.30 tonnes/hour. The main limiting factors are the high repair time, averaging 103.5 minutes per day, and the hard, rocky nature of the saprolite, which causes crusher components to wear out more quickly. Consequently, the production target of 2.5 tonnes per day has never been achieved. Optimisation efforts are required, including improving the effectiveness of equipment maintenance, ensuring a consistent feed rate, and handling the feed material before it enters the crusher.